Studies of electrical properties of low-resistivity sandstones based on digital rock technology. (18th January 2018) - Yan, Weichao; Sun, Jianmeng; Zhang, Jinyan; Yuan, Weiguo; Zhang, Li; Cui, Likai; Dong, Huaimin
Abstract: Electrical properties are important parameters to quantitatively calculate water saturation in oil and gas reservoirs by well logging interpretation. It is usual that oil layers show high resistivity responses, while water layers show low-resistivity responses. However, there are low-resistivity oil zones that exist in many oilfields around the world, leading to difficulties for reservoir evaluation. In our research, we used digital rock technology to study different internal and external factors to account for low rock resistivity responses in oil layers. We first constructed three-dimensional digital rock models with five components based on micro-computed tomography technology and x-ray diffraction experimental results, and then oil and water distributions in pores were determined by the pore morphology method. When the resistivity of each component was assigned, rock resistivities were calculated by using the finite element method. We collected 20 sandstone samples to prove the effectiveness of our numerical simulation methods. Based on the control variate method, we studied the effects of different factors on the resistivity indexes and rock resistivities. After sensitivity analyses, we found the main factors which caused low rock resistivities in oil layers. For unfractured rocks, influential factors arranged in descending order of importance were porosity, clay content, temperature, water salinity, heavy mineral, clay type and wettability. In addition, we found that the resistivity index could not provide enough information to identify a low-resistivity oil zone by using laboratory rock–electric experimental results. These results can not only expand our understandings of the electrical properties of low-resistivity rocks from oil layers, but also help identify low-resistivity oil zones better.